Quem tem direito à moradia? :uma análise da política nacional de habitação e dos programas de habitação de interesse social (2003-2005) - Siqueira, Ana Lúcia de Souza (2006)
This dissertation analyses the Brazilian housing policy of today s, focusing on the programmes in the socalled Social Interest Housing Subsystem in order to discuss to what extent the government has been able to grant housing constitutional rights in the country. The discussion is about housing policy and the principles in the country s Constitution regarding the role of housing as a social right, a right that must be granted by the state. This refers to land rent theory to understand the relationship between capital and property and the reasons why, under capitalism, housing becomes a commodity in the market. Then, it discusses the national housing policy, which emphasizes land ownership through financing, that is, via market, a process that excludes all low income population. In the conclusion, it is clear that, although government programmes cover extensively at least potentially the national territory as well as social group, subsidized housing programmes cannot be implemented in the city due to land prices because subsidy is too low. In this way, the law that grants housing rights to all Brazilian citizens is violated